2017
DOI: 10.1111/pedi.12560
|View full text |Cite
|
Sign up to set email alerts
|

Early transition from insulin to sulfonylureas in neonatal diabetes and follow-up: Experience from China

Abstract: Molecular genetic diagnosis is recommended in all patients with NDM. However, if genetic testing results are delayed, sulfonylurea therapy should be considered before such results are received, even in infants with newly diagnosed NDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…Of the seven patients carrying chromosome abnormalities, six (85.71%) were NDM, whereas only case 46 with a de novo 4p15.1 gross duplication was "infantile onset" diabetes with age of onset at 10 months. Among the five different chromosome abnormalities, 6q24 abnormalities (pUPD or duplication) were identified in four patients with NDM; a 11.76 Mb deletion at 1p36.23p36.12 was found in case 31 with symptoms of congenital heart disease, dysmorphic craniofacial features and psychomotor retardation, which had already been described in our previous report 17 ; a 17p13.3 duplication was found in case 32; and a 4p15.1 duplication was detected in case 46 (table 2 and online supplementary table S1).…”
Section: Genetic Spectrumsupporting
confidence: 64%
“…Of the seven patients carrying chromosome abnormalities, six (85.71%) were NDM, whereas only case 46 with a de novo 4p15.1 gross duplication was "infantile onset" diabetes with age of onset at 10 months. Among the five different chromosome abnormalities, 6q24 abnormalities (pUPD or duplication) were identified in four patients with NDM; a 11.76 Mb deletion at 1p36.23p36.12 was found in case 31 with symptoms of congenital heart disease, dysmorphic craniofacial features and psychomotor retardation, which had already been described in our previous report 17 ; a 17p13.3 duplication was found in case 32; and a 4p15.1 duplication was detected in case 46 (table 2 and online supplementary table S1).…”
Section: Genetic Spectrumsupporting
confidence: 64%
“…In China, Li et al. reported that the genetic etiology could be determined in 84% (19/23) of Chinese patients with neonatal diabetes mellitus, which was higher than the outcomes from Cao et al. (60%; 15/25).…”
Section: Introductionmentioning
confidence: 79%
“…The overexpression of genes at chromosome 6q24 is the most common cause of transient neonatal diabetes mellitus (OMIM 601410), which encompasses 70% of all cases. Basic and clinical studies suggest that sulfonylurea can help with the closing of the adenosine triphosphate‐sensitive potassium channel, and improve glycemic control and neurological outcomes, which was also confirmed in Chinese patients. Thus, molecular diagnosis is vital for accurate diagnosis and prognosis assessment for neonatal diabetes mellitus.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations